Analysis of social mobility in beneficiaries of social assistance programs in Colombia (2022)
Social assistance programs focus on the most vulnerable population, and it is precisely there where poverty, inequality and low social mobility persist. In Colombia, the latest adjustment to the method of targeting social assistance programs promises to improve its errors in focus and quality of information, although it is questioned whether this really leads to improving social assistance or only seeks the efficiency of public spending. The purpose of this work is to analyze the low social mobility in beneficiaries of social assistance programs and, based on the literature reviewed and the information available from the SISBEN IV survey, to approach the possible causes of this problem.